Bugle Resounding : Music and Musicians of the Civil War Era - Kelley, Bruce C.; Snell, Mark A. (Book collections on Project MUSE., 2004)
"Although numerous academic resources examine the music and musicians of the Civil War era, the research is spread across a variety of disciplines and is found in a wide array of scholarly journals, books, and papers. It is difficult to assimilate this diverse body of research, and few sources are dedicated solely to a rigorous and comprehensive investigation of the music and the musicians of this era. This anthology, which grew out of the first two National Conferences on Music of the Civil War Era, is an initial attempt to address that need."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.